Sustained reduction in health care costs after adjunctive treatment of graded intensive short-term dynamic psychotherapy in patients with psychotic disorders. Issue 3 (30th August 2015) - Abbass, Allan; Bernier, Denise; Kisely, Steve; Town, Joel; Johansson, Robert
Abstract: The aim of this pilot study was to evaluate the changes in symptom severity and long-term health care cost after intensive short-term dynamic psychotherapy (ISTDP) individually tailored and administered to patients with psychotic disorders undergoing standard psychiatric care. Eleven therapists with different levels of expertise delivered an average of 13 one-hour sessions of graded ISTDP to 38 patients with psychotic disorders. Costs for health care services were compiled for a one-year period prior to the start of ISTDP (baseline) along with four one-year periods after termination. Two validated self-report scales, the Brief Symptom Inventory and the Inventory of Interpersonal Problems, were administered at intake and termination of ISTDP. Results revealed that health care cost reductions were significant for the one-year post-treatment period relative to baseline year, for both physician costs and hospital costs, and the reductions were sustained for the follow-up period of four post-treatment years. Furthermore, at treatment termination self-reported symptoms and interpersonal problems were significantly reduced. These preliminary findings suggest that this brief adjunctive psychotherapy may be beneficial and reduce costs in selected patients with psychotic disorders, and that gains are sustained in long-term follow-up. Future research directions are discussed. Highlights: Intensive short-term dynamic psychotherapy may assist patients with psychotic disorders. Physician and hospital costs were significantly reduced following this talking treatment. Cost reductions were sustained in 4 year follow-up.